Analisis Probabilitas Sikap Indonesia Terhadap Pemerintahan Taliban Di Afghanistan Tahun 2021 - Ida Susilowati; Muh Zulfadillah Alvarezel; Rafif Ibnu Widyadana; Syahril Ady Fahlanda Siregar (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
Shortly after the withdrawal of US troops in Afghanistan, the Taliban quickly occupied the Afghan capital, Kabul. President Biden's decision to withdraw these troops from Afghanistan has attracted a lot of attention from various parties. Indonesia as a Muslim-majority country of course needs to determine its attitude towards the Taliban's rule. This journal analyzes the probability of Indonesia's attitude towards the Taliban government after the withdrawal of US troops in Afghanistan. The method used is descriptive qualitative with literature study data collection techniques. The results show that Indonesia tends to focus on establishing peace and upholding the rights of every citizen in Afghanistan. This is viewed from the principle of Indonesia's foreign policy which is